PMO-121 Osteopontin promotes natural killer T (NKT) cell accumulation in nonalcoholic steatohepatitis (NASH). (28th May 2012) - Liaskou, E; Claridge, L C; Younis, R; Shah, H; Shaw, J; Oo, Y H; Mi, Z; Kuo, P C; Canbay, A; Adams, D H; Diehl, A M; Syn, W K
Abstract : Introduction: Progressive steatohepatitis is characterised by increased inflammatory cell infiltration. Osteopontin (OPN) is a cytokine intricately associated with immune-cell accumulation, and we reported that NKT cells accumulate to promote hepatic injury in NASH. We hypothesise that OPN promotes NASH progression by supporting NKT migration across hepatic sinusoidal endothelium. Methods: Mice were fed chow or methionine-choline deficient (MCD) diet to induce NASH. After 4 weeks, mice were sacrificed; severity of disease assessed by serum aminotransferase (AST), liver OPN quantified by QRTPCR and immunohistochemistry, blood OPN measured by ELISA. In separate studies, MCD-fed mice were treated with sham or OPN aptamers, and FACS used to quantify liver NKTs. Primary human hepatic sinusoidal endothelial cells (HSEC) were stimulated with recombinant (r)OPN (0–1000 ng/ml), with or without TNFa (20 ng/ml)+IFNg (100 ng/ml), and expression of adhesion molecules (ICAM1, VCAM1) and chemokines (CXCL9, 10, 11, 16) assessed. To assess lymphocyte migration, lymphocytes were perfused over rOPN—or vehicle-treated-HSEC, with or without TNFa+IFNg. In separate experiments, TNFa+IFNg stimulated-HSEC were treated with OPN aptamers or blocking antibodies, and total lymphocyte adhesion recorded. Human NASH livers were immunostained for OPN, plasma measured for OPN, and liver NKT numbers from normal or NASH-cirrhotic patients quantified by FACS. Results: In mice, MCD-induced NASH upregulated expression of liver OPN by threefolds (p<0.05), blood OPN by twofolds (p<0.05), increased liver CD4 by 2.2-fold, and NKT cells by threefold (p<0.05). MCD-fed mice treated with OPN aptamers accumulated fewer CD4 and NKT cells (p<0.05), and exhibited attenuated injury (ALT: twofold reduction; p<0.02). rOPN induced expression of ICAM-1, VCAM-1 and CD31 on human HSEC, enhanced lymphocyte recruitment under conditions of flow (40%), and amplified recruitment ability of TNFa+IFNg stimulated HSEC (20%), while OPN neutralisation with RNA-aptamers reduced lymphocyte recruitment by 50% (all p<0.05). OPN effects were mediated via CD44, av b3, ICAM1, VCAM1, and CXCL16. In humans, liver and plasma OPN was significantly upregulated in NASH; livers from NASH-cirrhosis harboured twofolds more CD4 and threefolds more NKT cells (p<0.05) than normal. Conclusion: Liver and plasma OPN levels are upregulated during steatohepatitis in mice and humans, and promote liver NKT accumulation. OPN neutralisation significantly reduces lymphocyte subset recruitment and liver injury, suggesting that OPN is a promising anti-inflammatory target in steatohepatitis. Competing interests: None declared.